Carry-Over Effects of Desiccation Stress on the Oxidative Status of Fasting Anuran Juveniles - Prokić, Marko D.; Petrović, Tamara G.; Gavrilović, Branka R.; Despotović, Svetlana G.; Gavrić, Jelena P.; Kijanović, Ana; Tomašević Kolarov, Nataša; Vukov, Tanja; Radovanović, Tijana B. (Frontiers in Physiology, 2021)
Amphibians are sensitive to deteriorating environmental conditions, especially during transition to a terrestrial environment which is full of uncertainties. Harsh conditions, such as desiccation during earlier stages, affect different larval traits with possible carry-over effects on juvenile and adult life histories. The first consequences of the effects can be seen in juveniles in the challenges to find food and the ability to survive without it in a terrestrial habitat. Body size and the internal energy reserves acquired during the larval phase play an important role in this period. Herein, we tested how different water regimes (low water availability, desiccation and constant high-water availability) during larval development reflect on the oxidative status and ability of yellow belly toad (Bombina variegata) juveniles to endure short-term fasting. The desiccation regime significantly reduced the body size of metamorphs. The same was observed after two weeks of fasting, while the feeding treatment reduced differences mostly in the body mass of individuals from different water regimes. This was the result of a greater gain in mass in juveniles pre-exposed to desiccation. Pre-exposure to desiccation also modified the parameters of the antioxidant system (AOS) under feeding conditions, leading to higher values of superoxide dismutase, glutathione reductase and glutathione S-transferase, glutathione and sulfhydryl group concentrations, and lower glutathione peroxidase in comparison to juveniles reared under constant water. The increase in the AOS of juveniles can be considered as a physiological carry-over effect of desiccation, probably as the result of compensatory growth and/or earlier exposure to chronic stress. However, water levels during larval development did not exert significant effects on the oxidative status of juveniles subjected to food unavailability. Fasting juveniles, both control and desiccated, were exposed to oxidative stress, significantly higher lipid peroxide concentrations, lower superoxide dismutase, glutathione peroxidase, glutathione S-transferase, glutathione and sulfhydryl group values in comparison to feeding individuals. The lack of food in juvenile anurans activated the AOS response in the same manner, regardless of body size and stress pre-exposure, suggesting that the generally accepted hypothesis about the influence of metamorphic body size on the fitness of the postmetamorphic stage should be tested further.